Partially‐Saturated Brines Within Basal Ice or Sediments Can Explain the Bright Basal Reflections in the South Polar Layered Deposits. Issue 10 (14th October 2022) - Stillman, D. E.; Pettinelli, E.; Lauro, S. E.; Mattei, E.; Caprarelli, G.; Cosciotti, B.; Primm, K. M.; Orosei, R.
Abstract: Strong radar reflections have been previously mapped at the base of the Martian South Polar Layered Deposits. Here, we analyze laboratory measurements of dry and briny samples to determine the cause of this radar return. We find that liquid vein networks consisting of brines at the grain boundaries of ice crystals can greatly enhance the electrical conductivity, thereby causing strong radar reflections. A brine concentration of 2.7–6.0 vol% in ice is sufficient to match the electrical properties of the basal reflection as observed by Mars Advanced Radar for Subsurface and Ionospheric Sounding (MARSIS). When brine is mixed with sediments, the brine‐ice mixture in the pores must be 2–5 times more concentrated in salt, increasing the brine concentration to 6.3–29 vol%. Our best fit of the median observed MARSIS value suggests a salt‐bulk sample concentration of ∼6 wt%. Thus, salt enhancement mechanisms on the order of a magnitude greater than the Phoenix landing site are needed. To form brine, the basal reflector must reach a temperature greater than the eutectic temperature of calcium perchlorate of 197.3 ± 0.2 K, which may be possible if more complex thermal modeling is assumed. Colder metastable brines are possible, but stability over millions of years remains unclear. Conversely, gray hematite with a concentration of 33.2–59.0 vol% possess electrical properties that could cause the observed radar returns, but require concentrations 2–3 times larger than anywhere currently detected. We also argue that brines mixed with high‐surface‐area sediments, or dry red hematite, jarosite, and ilmenite cannot create the observed radar returns at low temperatures. Plain Language Summary: Previous research has detected strong radar reflections from the interface between Mars' southern ice cap and their underlying sediments over a region with an area of 20 × 30 km and 1.5 kms beneath the surface. Radar reflections are caused by changes in electrical properties. Here, we analyze electrical property laboratory measurements of materials under Mars‐like conditions. We find that a small amount of brine in ice samples could create strong radar reflections similar to those that are observed. A greater concentration of salt is needed in sediment‐ice mixtures. We suspect that the sublimation of a previous version of the ice cap may have deposited salt via sublimation in the base of the current ice cap. Additionally, the temperature at the base of the ice cap must be warmer than simple thermal models estimate, we suggest insulating materials such as CO2 ice may be incorporated into the ice cap. Additionally, dry gray hematite could also cause the observed radar returns, but must be even more concentrated than anywhere yet discovered on Mars. We can also rule out any brines mixed with clays, or dry red hematite, jarosite, and ilmenite as they cannot create the observed radar returns at low temperature. Key Points: Brines possess a significantly higher real part of dielectric permittivity and Direct Current (DC) conductivity than dry and frozen minerals Salt enhancements of 5–16 times the salt‐regolith concentration at the Phoenix landing site is needed in brine‐sediment mixtures The basal unit must be equal or greater than the eutectic temperature of calcium perchlorate (197.3 ± 0.2 K) to allow for brine formation